2004
DOI: 10.1379/459.1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of molecular chaperones in carbon tetrachloride–treated rat liver: implications in protection against liver damage

Abstract: Carbon tetrachloride (CCl 4 ) induces liver damage, apparently through the formation of free-radical metabolites. Molecular chaperones such as heat shock protein (Hsp) of 70 kDa have been found to protect cells from various stresses. We previously found that cytosolic chaperone pairs of the Hsp70 family and their DnaJ homolog cochaperones prevent nitric oxide-mediated apoptosis and heat-induced cell death. Expression of cytosolic chaperones, including Hsp70; heat shock cognate (Hsc) 70; and DnaJ homologs dj1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Japanese flounder fed diets supplemented with LF rather than LF-free ones reportedly showed significantly higher levels of heat shock proteins (HSP70s), which is regarded as a general primary cellular event in the liver tissue in response to stress (Iwama, Vijayan, Forsyth, & Ackerman, 1999;Yokoyama et al, 2005). HSP acts as a regulator of liver functioning under stressful conditions (Lee et al, 2004). Consequently, it is expected that higher levels of synthesized of orally administrated LF on liver functions (Burrin, Wang, Heath, & Dudley, 1996;Tsubota et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Japanese flounder fed diets supplemented with LF rather than LF-free ones reportedly showed significantly higher levels of heat shock proteins (HSP70s), which is regarded as a general primary cellular event in the liver tissue in response to stress (Iwama, Vijayan, Forsyth, & Ackerman, 1999;Yokoyama et al, 2005). HSP acts as a regulator of liver functioning under stressful conditions (Lee et al, 2004). Consequently, it is expected that higher levels of synthesized of orally administrated LF on liver functions (Burrin, Wang, Heath, & Dudley, 1996;Tsubota et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…33 Similar to DDC, the human MDB inducer ethanol leads to no or limited chaperone induction, 34,35 whereas liver chaperone levels are regularly elevated in multiple acute and chronic stress conditions. [36][37][38] Therefore, the low chaperone levels in DDC-fed or chronic alcohol-consuming individuals may facilitate aggregate formation by decreasing chaperone function (Fig. 3) and levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yenari 24) suggested that the increased expression of HSP-70 is an indicator of cellular stress. HSP-70 expression is elevated predominantly in the ischemic penumbra area 17 , 18) , and deletion of the HSP-70 gene exacerbates apoptosis after focal cerebral ischemia in mice 7) . It has recently been demonstrated that HSP-70 protects the brain against ischemia via an anti-inflammatory mechanism 4) .…”
Section: Discussionmentioning
confidence: 98%